Design of a linear low drop out (LDO) voltage regulator - Lawrence, Jennifer. (2010)
The drastic increase in the use of battery powered portable devices has required electronic devices to be able to work in low voltage environment. Power management systems are then becoming more crucial in those devices. These power management systems usually contain several low dropout voltage regulators (LDO).